The challenges to liberty, equality and fraternity in the time of Covid-19 and the encyclical letter Fratelli Tutti - Petzold-Pernía, Hermann (Frónesis, 2022)
I believe that, as the Holy Father Francis makes clear in the Encyclical Letter Fratelli Tutti, it is indispensable to have a thorough knowledge of the nature and definition of the concepts of liberty, equality and fraternity, and, therefore, their study is not a mere intellectual game or an erudite theoretical analysis without transcendence in an era of great challenges for suffering Humanity, since it is not a matter of censuring for the sake of censuring the governmental measures of the various states of the orb in the war against the COVID pandemic that impose social distancing, residential confinement and restrictions on the intra- and extra-urban movement of people, but to demand, on the one hand, that these measures be dictated in accordance with constitutional and legal norms and that their reasonableness be evident and, on the other hand, that access to hospital institutions, prompt medical attention and due therapeutic treatment (including the timely application of some of the vaccines in circulation worldwide) be effectively guaranteed for all people without discrimination of any kind.